Aerodynamic forces and wake structure on a 2D model of a vehicle in ground effect - Solís-García, Pedro; Zerzeri, Khaled; Nouailli, Mariem; Parras-Anguita, Luis; Durán-Venegas, Eduardo (My University, 2023)
In this research we perform numerical simulations and wind tunnel experiments of a D-shaped bluff body. Different flow conditions and ground-body distances are considered to analyse the ground effect on aerodynamic forces and wake structure.
Keywords: Aerodinámica; Aerodynamics; CFD; Vehicle